Efeitos do mercúrio sobre a atividade das enzimas alanina aminotransferase, lactato desidrogenase e glicose 6-fosfatase de ratos jovens - Silva, Lucélia Moraes e (2010)
Mercury is an environmental contaminant, and may accumulate in living organisms causing several damage. Studies have shown that this metal causes several physiological and biochemical alterations in young rats which are prevented by zinc. Thus, this work investigated the in vivo and in vitro effects of HgCl2 and ZnCl2 on alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and glucose 6-phosphatase (G6Pase) activities from liver and kidney of young rats to verify if the physiological and biochemical alterations induced by mercury, and prevented by zinc, are related to hepatic and renal metabolism. Glycemia and tissue glycogen levels (liver, kidney and muscle) were also monitored. Wistar rats were treated (s.c.) with saline or ZnCl2 (27 mg/kg/day) and with saline or HgCl2 (5.0 mg/kg/day) from 3rd to 7th and 8th to 12th days of age, respectively. Pups were sacrificed 24h after the last dose and samples were collected (blood, liver, kidney and muscle). For in vitro experimentation, the samples were collected similarly, with rats of 10 to 13 days old. Regarding in vivo experiments, the mercury treated rats presented an increase around 6 folds of the hepatic ALT activity, without alteration of renal ALT and hepatic LDH activities. Still, the mercury exposure significantly increases in 75% the G6Pase activity. The other parameters, glucose and glycogen, were not altered. The pre-exposure to zinc prevented totally the increase of liver ALT activity and partly the increase of hepatic G6Pase activity induced by mercury. In vitro results revealed that the serum and liver ALT and liver and kidney G6Pase activities were inhibited by mercury. The inhibitory effect may be related to chemical modification of sulfhydryl group of cysteine, since the mercury has great affinity for these groups, which contributes to its toxicity. Zinc inhibited liver and serum ALT activities in concentration of 100 μM. These results show that mercury induces distinct alterations in these enzymes when tested in vivo or in vitro, as well as when different sources of enzyme were used, hepatic and renal. The increased hepatic ALT and G6Pase activities suggest that animals exposed to mercury have an increased gluconeogenic activity in this tissue. Zinc prevents the in vivo effects of mercury on metabolic changes, confirming its important preventive role.